Creating An Environmentally Literacy Oriented E-Magazine on Household Waste Materials - Rahmi Rahmawati; Yulia Sukmawardani; Riri Aisyah (International Journal of Learning Media on Natural Science (IJLENS), 2024)
This study aims to describe the appearance, analysis of the results of the validation test and the analysis of the results of the feasibility test of e-magazine environmental literacy oriented on the topic household waste. This study uses the DBR (Design Based Research) method through the preliminary stages (analysis and deepening of the material), design (initial product manufacture), and development (validation test and feasibility test product). The resulting product is an e-magazine environmental literacy oriented on household waste material entitled "Household Waste Management". The validation test was carried out by three validators consisting of material expert lecturers and media experts. The average value of rcount of the validation test results for material, language and media display aspects is 0.87; 0.78; 0.89 which indicates that the e-magazine made is valid. Furthermore, a feasibility test was carried out on 20 students consisting of 10 students of chemistry education who were taking courses in waste management and treatment and 10 students outside of chemistry education who were randomly selected. The average value of the feasibility test results from the aspect of material, language and media display respectively is 97.00%, 97.50%; 95.00%. This shows that the emagzine environmental literacy oriented on the topic household waste that is made is declared very feasible to be used as a learning medium.